Fire Hazard Vulnerability Assessment of Commercial High-Rise Buildings of Dhaka, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2025)
A detailed building survey was conducted to assess the fire hazard vulnerability of high-rises in the Banani area of Dhaka. Assessments were done by interviewing building management and experts. The building was rated based on thirty-three indicators. The study reveals that around 47% of the surveyed buildings are in a high level of vulnerability. The remaining 37% are medium, and around 16% are less vulnerable. All the buildings constructed before 1993 (before the drafting of the BNBC—Bangladesh National Building Code and any act and regulation of fire protection and prevention) are highly vulnerable. The buildings constructed between 1993 and 2006 (the fire protection and prevention law-2003 came into force), before the enactment of the BNBC, 62% were in medium, and the rest (38%) were in high vulnerability level. Those were constructed after the enactment of BNBC (Dhaka Mohanagar Building (construction development, protection, and removal) Rule 2008 also enforced); only 12.5% are high, 50% medium, and 37% less vulnerable. We found that safety regulations (BNBC, building construction rules) and properly implementing the fire safety act/rules can drastically enhance safety standards. Policymakers and other stakeholders can find this research outcome helpful regarding fire safety enforcement.J. Asiat. Soc. Bangladesh, Sci. 51(1): 1-17, June 2025